Lora Enable Air Quality Monitoring Network for Smart City - Muhammad Afiq Azman,; Huda A Majid, (Progress in Engineering Application and Technology, 2025)
This project introduces the LoRa Enable Air Quality Monitoring Network for Smart City, an innovative Internet of Things (IoT) solution that utilizes Long Range (LoRa) communication technology for real-time urban air quality monitoring. The system measures environmental parameters including particulate matter (PM1.0, PM2.5, PM10), volatile organic compounds (VOCs), temperature, and humidity. It integrates low-power sensors and a centralized platform for cost-effective, scalable, and energy-efficient monitoring. The project aims to deploy and validate the system in urban locations, ensuring accurate data collection and long-range communication. Leveraging cloud technology, the collected data will be visualized through dashboards and reports to provide actionable insights. The ultimate goal is to identify pollution hotspots, aid policymakers in urban planning, and enhance public awareness of air quality, demonstrating a sustainable and scalable solution for smart city objectives and a healthier urban environment. The project successfully deployed and validated the system in real-world conditions, demonstrating accurate real-time data acquisition and long-range transmission of environmental parameters, as evidenced by successful data reception on The Things Network (TTN) console and efficient processing via Node-RED. Data visualization through Grafana dashboards confirmed the system's capability to provide actionable insights. The results highlight the system's efficiency, reliability, and scalability, emphasizing its potential to identify pollution hotspots, assist policymakers in urban planning, and improve public awareness of air quality issues, ultimately contributing to a healthier urban environment.